Estudo de preditores antropométricos para apneia obstrutiva do sono em crianças e adolescentes saudáveis e de parâmetros fotoantropométricos em crianças com síndrome congênita do Zika vírus e sua relação com dados polissonográficos - Lopes, Luiza Lassi de Araújo (2023)
Objectives: This study aimed to evaluate which anthropometric measurements (AMs) are most associated with increased predisposition to develop obstructive sleep apnea (OSA) in healthy children and adolescents, based on a systematic review with meta-analysis, as well as to evaluate polysomnographic aspects and photoanthropometrics in children with congenital Zika virus syndrome (CZVS). Materials and methods: Initially, a systematic review was performed with subsequent meta-analysis (PROSPERO #CRD42022310572) based on research in eight main databases and gray literature. In the second study, two groups composed of 7 children with SCZV (GCZVS) and 28 non-syndromic children as a control group (GCON) were submitted to a photoanthropometric analysis, based on facial photographs. All GCZVS patients underwent type I polysomnography (PSG) and had their photoanthropometric data correlated with quantitative PSG measurements. Results: Considering the systematic review, in eight studies with healthy children and adolescents and low to high risk of bias, the following MAs were reported: body mass index (BMI), neck circumference (NC), hip circumference (HC), waist-to-hip ratio (WHR), neck-to-waist ratio (NWR), waist circumference (WC), waist-to- height ratio (WHER) and facial AMs. The meta-analysis showed that the OSA group had an average of 1.00 cm greater for the NC (p < 0.001; Cohen's d = 2.26 [0.72, 5.23]), 3.07 cm greater for the WC (p = 0.030 ; Cohen's d = 0.28 [0.02, 0.53]), 3.96cm greater for the HC (p = 0.040; Cohen's d = 0.28 [0.02, 0.55]), 5.21o greater for the cervicomental angle (p = 0.020; Cohen's d = 0.31 [0.03, 0.59]) and 1.23o greater for the maxillomandibular angle (p < 0.001; Cohen's d = 0.47 [0 .22, 0.72]) than the control group. The mandibular depth angle was reduced by 1.86° (p = 0.001; Cohen's d = -0.36° [-0.65, -0.08]) in the control than in the OSA patients. BMI (p = 0.180), WHR (p = 0.280), NWR (p = 0.070), maxillary depth angle (p = 0.250) and upper/lower facial height ratio (p = 0.070) showed no significant difference between groups. In the second study, GSCZV patients had lower values for mean facial height in relation to the horizontal facial reference (HFR) (p = 0.025), chin height in relation to mid and lower face height (p = 0.000), vertical position of the ears in relation to HFR (p = 0.008), and higher values for nasal inter-wing distance in relation to HFR (p = 0.011), maxilla prominence (p = 0.008), nasolabial distance in relation to the vertical facial reference (VFR) (p = 0.001), mouth width in relation to HFR (p = 0.038), chin prominence (p = 0.017), vertical length of ears in relation to VFR (p = 0.004) and width of ears in relation to length jaw (p = 0.038). There was a statistically significant correlation for most photoanthropometric parameters with quantitative PSG data in the GSCZV. A total of twelve positive and seven negative correlations were observed. Conclusions: A critical analysis of the scientific evidence found that healthy children and adolescents with OSA had greater differences in means compared to controls, notably for the neck circumference outcome, the only one with high certainty of evidence. Thus, future studies with well-designed methodologies are needed to better elucidate the association between AMs and OSA. In addition, through the case-control study carried out, it was observed that the methodology based on facial photographs can help in the phenotypic description of patients with SCZV, as well as in the association of photoanthropometric parameters with quantitative PSG data associated with the development of to OSA.